Engenharia de requisitos aplicada em sistema legado de gestão e custeio de propostas comerciais: pesquisa-ação em empresa do setor de estamparia - Oliveira, Paulo Henrique Ribeiro de (2016)
The effort spent in maintaining systems regarded as legacies is relatively higher than that of new projects development effort. Such systems should be kept in place because, in most cases, are difficult to replace, given the complexity of changing the interaction and the impact on the functioning of processes, ie, the system can not stop. Thus, maintenance or modifications represent a sign of success for a Legacy System because it means that it is still useful and worth investing resources to keep it updated and running. However, if changes are carried out due to an emergency on business dynamics, and proper documentation is not completed, problems involving control and management of future maintenance might arise. In this context, it is the Requirements Engineering´s responsibility, as a sub-area of Software Engineering, to improve processes by proposing methods, tools and techniques that promote the development of the Requirement´s documentation, so that the requirements are in accordance with the satisfaction of stakeholders, meeting the business attributes in question. The objective of this work was to apply the Requirements Engineering in Legacy Systems of Management and Costing Methods of Sales Proposals in the stamping industry. Through literature review, document analysis and action research, the study was divided into four phases considering the development of the Sales Proposal Management and Costing Method System and three maintenance stages performed with the application of Requirements Engineering. In the first phase, a group of artifacts was generated expressing all system features. In the second phase, a progressive maintenance incorporated new features based in the system´s backlog with requirements collected in the first phase. The third phase included a new stamping business area that was not present in the initial development. Lastly, the fourth phase included new maintenance adjustments that answered to the needs of the stamping business system. The results of the study phases proved that the processes described in the Requirements Engineering (RE) were present in the information gathering actions, analysis, documentation and verification and validation of requirements, bringing academic and technical knowledge on issues related to legacy systems, ER and Software Engineering. As a result, it was concluded that the Requirements Engineering can be applied to Legacy Systems of Management and Costing Methods of Sales Proposals in stamping company in the industry.